Energy Policy and Regional Inequalities in the Brazilian Economy - Gervasio Santos; Eduardo Haddad; Geoffrey Hewings (European Regional Science Association (ERSA), 2010)
The objective of this paper is to evaluate the long-run regional impacts of tariff policy of the Brazilian electric power sector. The structural reforms carried on this sector determined the emergence of two different spatial distribution trends of the electric power tariffs among the Brazilian states: one of convergence and another of spatial divergence. The regional dispersion of tariffs is being influenced by the spatial features of the Brazilian economy, which is marked by the high degree of spatial concentration and the hierarchical distribution of large markets on the space. In spite of this, the electric power price differentials in Brazil tend to be determined by the market size differentials, which provide different conditions for gains from economies of scale by the electric power distribution companies. Based on these elements and in the fact that electric power is an important input for the production process, an Interregional Computable General Equilibrium model for energy policy analysis was built. The simulations showed that the input-output linkages, the spatial heterogeneity of the electric power intensity and the regional energy substitution differentials are the main determinants of spatial impacts of electric power price changes in Brazil. On the other hand, the recent trend of spatial divergence of the electric power prices may be contributing to reduce the national real GDP and to increase the regional inequalities in Brazil.
Keywords: P25; P28; C68; R13; 330; energy policy; regulation; spatial concentration; CGE modeling